2023
DOI: 10.3399/bjgp.2023.0150
|View full text |Cite
|
Sign up to set email alerts
|

Team-based continuity of care for patients with hypertension: a retrospective primary care cohort study in Hong Kong

Abstract: Background: Continuity of care (COC) is associated with improved health outcomes in hypertension patients. Team-based COC allows more flexibility in service delivery but there is a lack of research on its effectiveness for hypertension patients. Aim: This study aimed to investigate the effectiveness of team-based COC on cardiovascular disease prevention in patients with hypertension. Design and setting: A retrospective cohort study in primary care setting. Methods: 421,640 patients visiting public primary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…A few studies in the literature have highlighted the impact of having personal providers for BP control. A retrospective study conducted by Wanchun Xu et al 25 in Hong Kong not only suggested a link between continuity of care and reduced cardiovascular disease risk but also indicated an overall decline in the mortality rate associated with hypertension. Moreover, a study in Colombia underscored the correlation between continuity of care and effective BP control within primary care services.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies in the literature have highlighted the impact of having personal providers for BP control. A retrospective study conducted by Wanchun Xu et al 25 in Hong Kong not only suggested a link between continuity of care and reduced cardiovascular disease risk but also indicated an overall decline in the mortality rate associated with hypertension. Moreover, a study in Colombia underscored the correlation between continuity of care and effective BP control within primary care services.…”
Section: Discussionmentioning
confidence: 99%
“…Research claims that patients with chronic diseases benefit from all types of CoC, 18 22 although evidence is limited on whether patients benefit from disease-related or overall CoC. In a previous study on patients with asthma, chronic obstructive pulmonary disease (COPD), diabetes mellitus, and heart failure, this author group demonstrated lower mortality associated with higher chronic care continuity in the overall healthcare system.…”
Section: Introductionmentioning
confidence: 99%